PENINGKATAN SOFT SKILLS MELALUI MODEL PEMBELAJARAN GENERATIF PADA PELAJARAN FISIKA KELAS XI MIPA 1 SMA BABUSSALAM PEKANBARU - Ratih Septiara Ratih Septiara; Hendar Sudrajat Hendar Sudrajat; Muhammad Nasir Muhammad Nasir (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : This study aims to determine the effectiveness of the application of the generative learning model to increase the soft skills of students on class eleven science 1 at SMA Babussalam Pekanbaru. The study was conducted in high school Babussalam Pekanbaru from May to September 2015 by using one group pretest-posttest design applied to a single class. The subjects are consisted of 31 female students. Data was collected by given questionnaire before and after implementation of generative learning model. This research showed that there was an increasing on the student’s soft skills scores that marked gain of 0.46. Increasing the ability of individual students is dominated by a student who has a Gain on high effectiveness category that is 12 students. Observing from the aspect grain acquired skills picture that to clause 0.2 Gain communication skills obtained with very low category. For grain aspect of problem solving skills gained Gain 0.6 with the high category. For the aspect grain Gain 0.4 collaboration skills gained with low category. For the aspect grain leadership skills gained Gain 0.6 with the high category. It can be concluded that the generative learning module is effective for increasing the soft skills of students on class eleven science 1 at SMA Babussalam Pekanbaru.Key Words : Physics, Soft skills, Generative learning